Enhancing the Competitiveness of Ceramic MSMEs through Accounting and Tax Literacy: Evidence from the Plered Ceramic Cluster - Anna, Yane Devi; Puryati, Dwi; Said, Lina; Homan, Hery Syaerul (Jurnal Pengabdian UNDIKMA, 2026)
This community service activity aims to improve the accounting and tax literacy of micro, small, and medium-sized enterprise (MSME) operators to enable them to prepare accurate financial reports and establish competitive product pricing. The program involved 33 participants from the ceramics industry in Anjun Village, Plered District, Purwakarta Regency, Indonesia. The training was delivered through a combination of instructional sessions, interactive discussions, transaction-recording simulations, and practical cost of goods sold (COGS) calculations based on real-world case studies from the local ceramics industry. Program effectiveness was evaluated using pre-test and post-test assessments comprising ten indicators of accounting and tax literacy. The data were analyzed descriptively using percentage analysis to measure changes in participants’ understanding across the assessed indicators. The evaluation results showed that the average level of participants’ understanding increased from 50% in the pre-test to 63% in the post-test, with improvements observed in nine of the ten assessment indicators. In addition to improving technical competencies, the program also enhanced participants’ confidence in managing their business finances. Overall, the findings demonstrate that a needs-based and participatory training approach is effective in strengthening MSME accounting and tax literacy while fostering more accountable and competitive business management practices.